THE DEVELOPMENT OF ADMINISTRATOR LEADERSHIP BASED ON THE FOUR BRAHMAVIHARA UNDER KRABI PROVINCIAL OFFICE OF LEARNING ENCOURAGEMENT - Bunklong , Kasama; PhrakhruPhichitsupakarn; Yotharak, Maliwan (Journal of Educational Review Faculty of Education in MCU, 2025)
The objectives of the research article were 1) To study the leadership of school administrators under Krabi provincial office of learning encouragement, 2) To study the guidelines of development of school administrator leadership based on the four principles of Brahmavihra under Krabi provincial office of learning encouragement, 3) To present the guidelines for the development of school administrator leadership based on the Four Brahmavihra under Krabi provincial office of learning encouragement. It was a qualitative research with 3 research steps as follows: Step 1) studying the leadership conditions of school administrators. The data were collected through in-depth interviews with 15 relevant participants. Step 2) studying the guidelines for developing of school administrator leadership based on the Four Brahmavihra through in-depth interviews with 5 experts to draft the guidelines. The data were analyzed using content analysis based on the interview format. Step 3) presenting guidelines for the development of school administrator leadership based on the Four Brahmavihra through a group discussion consisting of 7 experts to ensure appropriateness, assess feasibility, and evaluate potential benefits. The data were analyzed using content analysis based on the guiding questions for the focus group discussion. The results showed that: 1) The state of leadership development among school administrators revealed several challenges in school operations. School administrators lack decision-making skills and sometimes used inappropriate language with subordinates. Teachers struggled with modern teaching methodologies due to not having a formal background in education and exhibit a lack of enthusiasm in adapting to new technologies. While some teachers possessed diverse skill sets, others have expertise only in specific areas, leading to disparities in instructional effectiveness. The elements of leadership identified were: (1) being a suitable role model, (2) intellectual stimulation, (3) having idealistic influence, (4) considering individuality, and (5) inspiring motivation. 2) The leadership development approaches for school administrators included five components with incorporating the Four Brahmavihra were applied together, which consisted of: (1) Mett (loving-kindness), the desire to free others from suffering, (2) Karuṇ (compassion), the desire for others to be free from suffering, (3) Mudit (sympathetic joy), rejoicing in others' success, and (4) Upekkh (equanimity), impartiality. 3) The proposed strategies for developing leadership based on the Four Brahmavihra of school administrators under Krabi provincial office of learning encouragement, as discussed in focus groups with 7 experts, were deemed feasible, appropriate, and beneficial for developing leadership in accordance with the Four Brahmavihra.